Pengaruh Menghilangkan Dinding Geser Terhadap Perilaku Stuktur Gedung 11 Lantai dengan Denah L-Shaped - Dhanarsari, R.A.N.; Indra, S.; Manaha, Y.P. (REKONSTRUKSI TADULAKO: Civil Engineering Journal on Research and Development, 2025)
Malang Regency is an area prone to tectonic earthquakes, so the planning of multi-story buildings, especially those with an asymmetric L-shaped plan, needs to consider the optimization of earthquake-resistant structures. Shear walls are commonly used to increase structural stiffness, but they can introduce complexities in planning and construction. This study aims to evaluate the effect of removing shear walls on the structural behavior of the Samaview Residence Building, an 11-story building with an L-shaped plan in Malang Regency. Structural analysis was carried out with the help of the ETABS 18 program using building technical data, material data, and building design drawings obtained from the implementer and literature studies. The analysis includes determining the dimensions of structural elements based on SNI 2847:2019, calculating gravity and earthquake loads according to SNI 1727:2020 and SNI 1726:2019, as well as evaluating inter-story drift, structural irregularities, and P-Delta effects. The analysis results show that the removal of the shear wall still results in structural element dimensions that meet the requirements of SNI 2847:2019. Structural drift and P-Delta effects also meet the requirements of SNI 1726:2019, although there are inside corner irregularities that need to be considered in the design. It can be concluded that removing the shear walls in the Samaview Residence Building does not affect the ability of the structure to withstand gravity and earthquake loads. However, special attention needs to be paid to the inner corner irregularities, drift, and P-Delta effects to ensure the effectiveness of the earthquake-resistant structural system